The Relationship Between Laboratory Management and Improving the Quality of Learning in College - Agustin, Silvi; Widiyasmoro, Adi; Supriyadi, Supriyadi; Zaharuddin, Zaharuddin (inovator, 2025)
Laboratory management in educational institutions is regulated in accordance with applicable regulations, governance and is applied consistently. This study aims to analyze the relationship between laboratory management and improving the quality of learning in college. Quantitative research with a survey approach involving 50 respondents using the Non Probability Sampling method with the Total Sampling technique. Data acquisition using student perception instruments on laboratory management and learning quality, analyzed using research hypothesis testing and correlational tests. The results of Sig, (2-tailed) <0.001 (less than 0.05) and Pearson Correlation 0.857 (more than 0.279 in the N = 50 table significance 5%) with a positive relationship indicating a significant relationship between the two variables. This study concludes that there is a significant relationship between laboratory management and improving the quality of learning in college.